FTO Facilitates Cervical Cancer Malignancy Through Inducing m6A‐Demethylation of PIK3R3 mRNA - Bingxin Chen; Liming Wang; Xiaomin Li; Ci Ren; Chun Gao; Wencheng Ding; Hui Wang (Cancer Medicine)
ABSTRACT Background The incidence rate and mortality of cervical cancer rank the fourth in the global female cancer. N6‐methyladenosine (m6A) always plays an important role in tumor progression, and fat mass and obesity‐associated gene (FTO) works as the m6A demethylase. Aims Our study aimed to narrate the biological function and potential mechanisms for FTO in cervical cancer malignancy. Materials & Methods We analyzed potential clinical value of FTO in cervical cancer patients. The relative protein levels of FTO in cervical cancerous tissue and paracancerous tissue were verified by IHC. After changing the FTO expression level by lentivirus transfection, the proliferation and metastasis ability of cervical cancer cells were detected both in vitro and in vivo. Further, Merip‐seq and Merip‐qPCR are used to profile m6A transcriptome‐wide. Finally, western blot were performed to identify the regulatory mechanism. Results Based on TCGA‐CESC cohort and GEO dataset, FTO expression levels in HPV‐positive cancer patients were significantly higher than those in HPV‐negative cancer patients and could predict advanced FIGO stage. The protein level of FTO in cervical cancerous tissue was higher than that in paracancerous tissue. Functional assays indicated that FTO promoted the proliferation, migration and invasion of cervical cancer cells both in vitro and in vivo. The Merip‐seq and Merip‐qPCR evoked that relative PIK3R3 m6A level was significantly increased after FTO knockdown, which effected the activation of FoxO pathway. After knocking down FTO, upregulation of PIK3R3 can restore the malignancy of cervical cancer. Conclusion All in all, these data suggest a vital role for FTO in occurrence and development of cervical cancer.